Remote teaching in times of pandemic - a case study of the Federal Institute of the South of Minas - campi Passos (Research, Society and Development, 2021)
The article aims to identify the perceptions that students at the Federal Institute of Southern Minas Gerais - Campi Passos, during the first semester of 2021, specifically in the subjects of General Theory of Administration I. For the construction of this material it was necessary the elaboration of a semi-structured questionnaire, containing 3 (three) closed questions, available via Googlegass, which was sent to the students, where the specified time for the answer was (5) days, during the month of July 2021, where all students responded, totaling 44 students. In conclusion, it was found that the model of teaching of this discipline allowed an important assessment in the methodology used, which offers subsidies for a global assessment by the teacher and serves as a guide for the Institution's managers. In addition, the points of excellence in the teaching-learning process and the necessary adjustments to be provided were identified, which suggests that the other subjects of the other courses offered by the institution be applied, respecting the methodologies used by the other teachers.